Elucidation of obstructive sleep apnoea related blood pressure surge using a novel continuous beat-to-beat blood pressure monitoring system. Issue 3 (8th March 2022) - Kwon, Younghoon; Baruch, Martin; Stafford, Patrick L.; Bonner, Heather; Cho, Yeilim; Mazimba, Sula; Logan, Jeongok G.; Shimbo, Daichi; Park, Sung-Ha; Lin, Gen-Min; Azarbarzin, Ali; Calhoun, David A.; et al.
Abstract : Background: Obstructive sleep apnoea (OSA) episode related blood pressure (BP) surge may mediate the association of OSA with cardiovascular disease. However, BP is not measured during a clinical sleep study. Method: We tested the feasibility of incorporating the Caretaker physiological monitor, which utilizes a novel continuous beat-to-beat (b-b) BP monitoring technology, into polysomnography (PSG) and aimed to characterize BP surges related to obstructive respiratory events. B-b BP was concurrently collected and merged with PSG data on a posthoc basis. We compared BP surge between mean respiratory (apnoea, hypopnea and desaturation-alone events) and nonrespiratory events (spontaneous or leg movement-related arousals). We examined the association of the degree of oxygen desaturation with BP surge in a given respiratory event combining all events. A total of 17 consecutive patients (12 men, mean 52 years old, nine diagnostic and eight split-night PSGs) undergoing clinically indicated PSG were included after excluding one patient with poor signal quality due to excessive movement. Results: Caretaker was well tolerated. Mean respiratory BP surge ranged from 5 to 19 mmHg [Median (IQR) = 13.9 (9.5–16.2)]. Mean BP surge between the respiratory and nonrespiratory events was similar [13.8 (4.5) vs. 14.9 (5.3) mmHg, P = 0.13]. Accounting for the count distribution of desaturation/BP surge data pair events, there was a linear correlation between the degree of oxygen desaturation and BP surge (R = 0.57, P < 0.001). In eight patients undergoing split-night sleep studies, the number of BP surge events (≥10 mmHg/h) decreased during continuous positive airway pressure in all but one patient. Conclusion: We demonstrated highly variable OSA-related BP surge patterns using the Caretaker's b-b BP monitoring technology that has the potential to be integrated into sleep studies.